Note on the Affine Group Representations (European Journal of Pure and Applied Mathematics, 2025)
The representation of the affine group is a crucial topic in harmonic analysis. In this paper, we use the wavelet transform to investigate the intertwining operator. This, approach helps compare different unitary representations of the affine group.
Keywords: Wavelet transforms; unitary representation